2012
DOI: 10.1029/2012je004178
|View full text |Cite
|
Sign up to set email alerts
|

Major‐element abundances on the surface of Mercury: Results from the MESSENGER Gamma‐Ray Spectrometer

Abstract: [1] Orbital gamma-ray measurements obtained by the MESSENGER spacecraft have been analyzed to determine the abundances of the major elements Al, Ca, S, Fe, and Na on the surface of Mercury. The Si abundance was determined and used to normalize those of the other reported elements. The Na analysis provides the first abundance estimate of 2.9 AE 0.1 wt% for this element on Mercury's surface. The other elemental results (S/Si = 0.092 AE 0.015, Ca/Si = 0.24 AE 0.05, and Fe/Si = 0.077 AE 0.013) are consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
141
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 160 publications
(146 citation statements)
references
References 45 publications
4
141
1
Order By: Relevance
“…, because gamma-ray attenuation is not significant for these angles for the 1779-keV Si peak [Peplowski et al, 2012], which is known to be dominated by planet-originating gamma rays [Evans et al, 2012]. The removal of off-nadir pointing data reinforces the bias of these measurements to northern regions, as it disproportionately removes data south of the periapsis latitude (see Figure 2).…”
Section: Messenger Gamma-ray Spectrometer Al Measurementsmentioning
confidence: 57%
See 1 more Smart Citation
“…, because gamma-ray attenuation is not significant for these angles for the 1779-keV Si peak [Peplowski et al, 2012], which is known to be dominated by planet-originating gamma rays [Evans et al, 2012]. The removal of off-nadir pointing data reinforces the bias of these measurements to northern regions, as it disproportionately removes data south of the periapsis latitude (see Figure 2).…”
Section: Messenger Gamma-ray Spectrometer Al Measurementsmentioning
confidence: 57%
“…[2] Gamma-ray spectroscopy is a well-established technique for the remote characterization of the elemental composition of planetary surfaces, as has been demonstrated by its successful utilization from orbit around the Moon [e.g., Bielefeld et al, 1976;Lawrence et al, 1998;Yamashita et al, 2010] and Mars and by the MErcury Surface, Space ENviroment, GEochemisty, and Ranging (MESSENGER) spacecraft at Mercury [Peplowski et al, 2011b;Evans et al, 2012]. The Dawn spacecraft is also carrying a gamma-ray spectrometer to characterize the surface compositions of asteroids 4 Vesta and 1 Ceres [Prettyman et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…Our calculations to correct the effect of sulfides on Ca and Mg concentrations in the silicate melt are thus probably the most conservative. Evans et al (2012) have reported a first average abundance estimate of ca. 2.9 wt% Na (3.9 wt% Na 2 O) on Mercury's surface.…”
Section: The Roles Of Sulfur and Iron Metalmentioning
confidence: 99%
“…First, this element reduces the liquidus temperature. The high average amount of Na (3.9 wt% Na 2 O) reported by Evans et al (2012) would also produce significantly different calculated mineral component. As illustrated in Fig.…”
Section: Low-pressure Differentiation Of Mercury Lavasmentioning
confidence: 99%
“…On this basis, it has been suggested that hollow-formation involves the loss of the 'darkening' agent within LRM [Blewett et al, 2013], which may be spectrally neutral (making LRM relatively 'blue' by counteracting the 'redness' of other components) [Blewett et al, 2009]. Calcium or magnesium sulfides are most commonly-cited as candidates for the relatively volatile substance [Blewett et al, 2011[Blewett et al, , 2013Helbert et al, 2012], on the basis of the high concentration of sulfur detected at Mercury's surface [Nittler et al, 2011;Evans et al, 2012], expectations for mineralogy under Mercury's highly reducing conditions [Burbine et al, 2002], and correlations between sulfur, calcium and magnesium abundance in heavily-cratered terrains [Weider et al, 2015]. This hypothesis has recently gained further support from observations of anomalously high exospheric calcium above the extensively-hollowed Tyagaraja crater [Bennett et al, 2016].…”
Section: Introductionmentioning
confidence: 99%